Mapping and distribution of the telomeric sequences (T2AG3 repeats) in the marsupialia famili Macropodidae - Rony Kunda; Mechiavel Moniharapon; Pieter Kakisina (Genetikawan Muda Indonesia, 2021)
Marsupial and monotreme mammals very important in vertebrate phylogeny studies between reptile-mammal divergence 310 million years ago (mya) and the eutherian (placental) mammal radiation 105 mya. They have many features including their distinctive chromosomes, which in marsupials are typically very large and well conserved between species. Monotreme genomes are divided into several large chromosomes and many smaller chromosomes, with a complicated sex chromosome models that forms a translocation chain in male meiosis. In Macropus genera members, telomeres have been shown to be involved in the fusion and inversion of chromosomes, but for Kangaroo, the telomere sequence remains consistent and does not change during the chromosomal fusion event, but this is not the case in mice. The ancestor of marsupials (plesiomorphic), has a karyotype of 2n=14, but for kangaroos and wallabies have a karyotype of 2n=22, based on fews curently research, we asserted that this karyotype is derived from the karyotype of marsupial ancestors who have a karyotype of 2n=14. Based on molecular genetic studies have shown that W. bicolor (swamp wallaby) is more appropriately grouped into the Macropus genera, not as a “sister” of Macropus genera. In addition Macropus and W. bicolor there has been a division of chromosomes due to chromosome fusion, but W. bicolor has fewer chromosomes than other members of Macropodidae, i.e (2n=10 for females, and 2n=11 for males).